Electrolyte and lithium battery

CN123018075APending Publication Date: 2026-10-30ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611114752.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,电压平台的不断提高,对相关电解液体系形成了严峻考验

Benefits of technology

[0016]为使本公开的目的、技术方案和优点更加清楚明白,以下结合具体实施例,对本公开进一步详细说明。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018075A_ABST
    Figure CN123018075A_ABST
Patent Text Reader

Abstract

The present disclosure provides an electrolyte and a lithium battery. Specifically, the electrolyte comprises a first additive and a second additive; the first additive is a compound as shown in formula (I): formula (I); in formula (I), R is independently selected from any one of the following groups: hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, and substituted or unsubstituted 3-8 membered heterocyclic group; the second additive is a compound as shown in formula (II): formula (II); through the synergistic reduction reaction of the first additive and the second additive on the negative electrode side, a composite SEI film rich in LiF and a strong organic skeleton is generated, thereby improving the fast charging performance and cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of battery technology, and more particularly to an electrolyte and a lithium battery. Background Technology

[0002] As electric vehicles increasingly demand higher driving ranges, the operating voltage of power batteries continues to rise in order to achieve higher energy densities. However, this continuous increase in voltage levels poses a severe challenge to the related electrolyte systems. Summary of the Invention

[0003] In view of this, the purpose of this disclosure is to provide an electrolyte and a lithium battery.

[0004] To achieve the above objectives, this disclosure provides an electrolyte comprising a first additive and a second additive; wherein,

[0005] The first additive is a compound represented by the following formula (I): Formula (I); In formula (I), R is independently selected from any one of the following groups: hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, and substituted or unsubstituted heterocyclic group from 3 to 8 members; when substituted, the substituent is selected from at least one of halogen, amino, cyano or silyl. The second additive is a compound as shown in formula (II): Formula (II).

[0006] In some embodiments, the heterocyclic group is selected from pyridine, cyclic carboxylic anhydrides, or imidazole; and / or and / or Based on the total mass of the electrolyte, the mass fraction of the first additive is 0.05% to 3%, and the mass fraction of the second additive is 1% to 17%.

[0007] In some embodiments, based on the total mass of the electrolyte, the mass fraction of the first additive is 0.1% to 0.5%; and the mass fraction of the second additive is 5% to 10%.

[0008] In some embodiments, the compound represented by formula (I) comprises at least one of the following structural formulas: Formula (Ⅲ), Formula (Ⅳ) Formula (V) Formula (VI).

[0009] In some embodiments, a third additive is further included, said third additive being a compound of formula (VII): Formula (VII); Based on the total mass of the electrolyte, the mass fraction of the third additive is 0.05% to 3%.

[0010] In some embodiments, the mass fraction of the third additive is 0.1% to 0.5% based on the total mass of the electrolyte.

[0011] In some embodiments, a fourth additive is also included, the fourth additive comprising at least one of lithium difluorobis(oxalato)phosphate, tris(trimethylsilyl)phosphate, and lithium difluorophosphate.

[0012] In some embodiments, a solvent is also included; the solvent includes at least one of carbonates and carboxylic esters.

[0013] In some embodiments, the carbonate includes dimethyl carbonate; Based on the total mass of the electrolyte, the mass fraction of dimethyl carbonate is 10% to 40%.

[0014] Based on the same inventive concept, this disclosure also provides a lithium battery, including any of the electrolytes described above and a ternary cathode material; wherein, in the ternary cathode material, the mass percentage of nickel is not less than 90% based on the total mass of metal elements other than lithium.

[0015] As can be seen from the above, the present disclosure provides an electrolyte and a lithium battery, wherein the electrolyte includes a first additive and a second additive; wherein the first additive is a compound represented by the following formula (I): Formula (I); in Formula (I), R is independently selected from any one of the following groups: hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, substituted or unsubstituted 3- to 8-membered heterocyclic group; when substituted, the substituent is selected from at least one of halogen, amino, cyano, or silyl; the second additive is a compound as shown in Formula (II): Formula (II); through the synergistic reduction reaction of the first and second additives on the negative electrode side, a composite SEI film rich in LiF and a robust organic framework is generated, which improves the fast charging performance and cycle stability of the battery. Detailed Implementation

[0016] To make the objectives, technical solutions, and advantages of this disclosure clearer, the following detailed description is provided in conjunction with specific embodiments.

[0017] It should be noted that, unless otherwise defined, the technical or scientific terms used in the embodiments of this disclosure should have the ordinary meaning understood by one of ordinary skill in the art to which this disclosure pertains. The terms "first," "second," and similar terms used in the embodiments of this disclosure do not indicate any order, quantity, or importance, but are merely used to distinguish different components. Terms such as "comprising" or "including" mean that the element or object preceding the word encompasses the elements or objects listed following the word and their equivalents, without excluding other elements or objects. Terms such as "connected" or "linked" are not limited to physical or mechanical connections, but can include electrical connections, whether direct or indirect. Terms such as "upper," "lower," "left," and "right" are used only to indicate relative positional relationships; when the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0018] It should be noted that, unless otherwise defined, the technical or scientific terms used in the embodiments of this disclosure should have the ordinary meaning as understood by one of ordinary skill in the art to which this disclosure pertains.

[0019] In this disclosure, the term "range" is used to define a range in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~130 and 70~120 are listed for a specific parameter, it is expected that ranges of 60~120 and 70~130 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this disclosure, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12.

[0020] Unless otherwise specified, all embodiments and optional embodiments of this disclosure can be combined to form new technical solutions.

[0021] Unless otherwise specified, all technical features and optional technical features of this disclosure can be combined to form new technical solutions.

[0022] Unless otherwise specified, the terms "comprising" and "including" as used in this disclosure can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0023] Unless otherwise specified, the term "or" is inclusive in this disclosure. For example, the phrase "A or B" means "A, B, or both A and B".

[0024] Terminology Explanation A solid electrolyte interface (SEI) is a passivation layer formed on the surface of the electrode material during the charging and discharging process of a lithium-ion battery, resulting from the reaction between the electrode material and the electrolyte at the solid-liquid interface. In some cases, it can specifically refer to the passivation layer located on the surface of the negative electrode. This passivation layer is an interface layer, exhibiting characteristics of a solid electrolyte; it is an electronic insulator but is actually a lithium electrolyte. + Li is an excellent conductor. + It can freely embed and extract through this passivation layer.

[0025] The cathode electrolyte interface (CEI) is an interface film formed on the surface of the positive electrode of a lithium battery. When the positive electrode material is at a high potential, it undergoes an oxidation reaction with the electrolyte, thereby forming an interface layer between the two, which has the function of preventing the electrolyte from continuously oxidizing under high voltage.

[0026] Direct current internal resistance (DCR) is the equivalent internal resistance of a battery under DC operating conditions. It reflects the battery's ability to impede DC current and can characterize the battery's dynamic performance. It is one of the important indicators of whether a battery can achieve long-term cycling.

[0027] As described in the background section, the continuous increase in voltage plateaus poses a severe challenge to related electrolyte systems. Specifically, conventional cyclic and chain carbonate solvents, such as ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC), while possessing good ionic conductivity and film-forming ability, have narrow electrochemical windows. When the charging voltage exceeds 4.2V (vs. Li / Li), the electrochemical window becomes narrower. +When the electrolyte is oxidized, the tendency for oxidation and decomposition at the positive electrode interface intensifies dramatically. This oxidation and decomposition process not only directly consumes the active lithium source, leading to irreversible capacity decay, but also triggers a series of adverse reactions: on the one hand, the oxidation of solvent molecules produces a large amount of CO2, CO and other gases, causing the battery to swell and internal pressure to rise, resulting in serious safety hazards; on the other hand, the continuous decomposition reaction will deposit a loose and unstable CEI film on the surface of the positive electrode. This film has high impedance and poor ion conductivity, which will further aggravate polarization, limit the rate performance of the battery, and cannot effectively inhibit the subsequent electrolyte decomposition and the dissolution of positive electrode transition metal ions, forming a vicious cycle of continuous performance deterioration.

[0028] High-voltage additives (such as various phosphorus- and sulfur-containing compounds) can broaden the antioxidant window of electrolytes to some extent. However, while using a single high-voltage additive can improve interfacial stability to some extent, the protective film formed often lacks sufficient mechanical strength. Under long-term cycling, especially under the stress of volume expansion of silicon-based anodes, it is prone to cracking and failure, making the protective effect difficult to sustain.

[0029] Utilizing novel fluorinated solvents to construct high-voltage electrolyte matrices is another alternative solution. Specifically, fluorinated solvents, such as 2,2-difluoroethyl acetate (DFEA) and methyl (2,2,2-trifluoroethyl) carbonate (FEMC), can significantly enhance the energy levels of molecular orbitals due to their strong electron-withdrawing effect, thus possessing intrinsically high oxidation stability. However, these solvents typically exhibit poor compatibility with anodes such as graphite and silicon-carbon, resulting in fragile SEI films with high impedance, leading to low initial battery efficiency, unsatisfactory cycle life, and limited low-temperature performance.

[0030] Therefore, the relevant technologies face a prominent contradiction: fluorinated solvent systems with high voltage tolerance are difficult to effectively synergize with film-forming components capable of constructing stable, low-impedance SEI / CEI films. Simple physical blending cannot resolve the competition and conflict of interfacial reactions at the molecular level, often resulting in a trade-off.

[0031] In view of this, embodiments of the present disclosure provide an electrolyte and a lithium battery, wherein the electrolyte includes a first additive and a second additive; wherein the first additive is a compound represented by the following formula (I): Formula (I); in Formula (I), R is independently selected from any one of the following groups: hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, substituted or unsubstituted 3- to 8-membered heterocyclic group; when substituted, the substituent is selected from at least one of halogen, amino, cyano, or silyl; the second additive is a compound as shown in Formula (II): Formula (II); through the synergistic reduction reaction of the first and second additives on the negative electrode side, a composite SEI film rich in LiF and a robust organic framework is generated, which improves the fast charging performance and cycle stability of the battery.

[0032] To make the technical solutions of this disclosure clearer and easier to understand, the electrolyte and lithium battery provided in this disclosure will be described in detail below with reference to specific embodiments.

[0033] Electrolyte In some embodiments, the electrolyte includes a first additive and a second additive; wherein the first additive is a compound represented by formula (I): Formula (I); in Formula (I), R is independently selected from any one of the following groups: hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, substituted or unsubstituted heterocyclic group from 3 to 8 members; when substituted, the substituent is selected from at least one of halogen, amino, cyano or silyl; The second additive is a compound as shown in formula (II): Formula (II).

[0034] For example, the halogen can be F, Cl, Br, etc. The substituted or unsubstituted amino group can be amino, dimethylamino, diethylamino, etc. The silyl group can be trimethylsilyl, etc. The unsubstituted alkyl group can be methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, etc. The unsubstituted alkenyl group can be vinyl, propenyl, butenyl, etc. The unsubstituted alkynyl group can be ethynyl, butynyl, etc. The group containing an ester group can be methyl ester, ethyl ester, acetoxy, etc. The group containing a carbonyl group can be formaldehyde, acetaldehyde, acetone, etc. The heterocyclic group can be pyrazole, furan, piperidine, aziridine, pyridine, cyclic carboxylic anhydride, imidazole, etc.

[0035] Optionally, the compound represented by formula (I) includes at least one of the following structural formulas: Formula (Ⅲ), Formula (Ⅳ) Formula (V) Formula (VI).

[0036] During the initial charge and discharge of the battery, the second additive in the electrolyte undergoes reducing CO bond cleavage at a lower potential, generating fluorinated alkoxy anions and alkyl radicals. The generated alkoxy anions are strong nucleophiles, immediately attacking the carbonyl carbon of the anhydride in the first additive, leading to anhydride ring opening. Thus, the first and second additives are synergistically reduced and decomposed on the negative electrode surface, jointly participating in the construction of a stable electrolyte interphase (SEI) membrane. The introduction of fluorinated fragments (e.g., LiF, fluorinated organic compounds) can significantly improve the ionic conductivity, chemical stability, and mechanical strength of the SEI membrane.

[0037] It can be seen that the thermodynamically stable first and second additives can be "activated" and interact under electrochemical conditions. The synergistic reduction reaction of the two on the negative electrode side can generate a composite SEI film rich in LiF and a robust organic framework in situ, which is beneficial to improving the fast charging performance and cycle stability of the battery.

[0038] In some embodiments, the mass fraction of the first additive, based on the total mass of the electrolyte, is 0.05% to 3%, for example, 0.05%, 0.1%, 0.3%, 0.5%, 0.75%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.5%, 3%, etc. Optionally, the mass fraction of the first additive, based on the total mass of the electrolyte, is 0.1% to 0.5%, for example, 0.1%, 0.2%, 0.25%, 0.3%, 0.4%, or 0.5%, etc. Lithium batteries prepared using such a mass fraction of the first additive exhibit superior performance.

[0039] In some embodiments, the mass fraction of the second additive, based on the total mass of the electrolyte, is 1% to 17%, for example, 1%, 3%, 6%, 8%, 10%, 12%, 14%, 15%, 17%, etc. Optionally, the mass fraction of the second additive, based on the total mass of the electrolyte, is 5% to 10%, for example, 5%, 7%, 8%, 9%, or 10%, etc. Lithium batteries prepared with such a mass fraction of the second additive exhibit superior performance.

[0040] In some embodiments, the electrolyte further includes a third additive, which is a compound of formula (VII): Formula (VII). It should be noted that the third additive can work synergistically with the first and second additives to enhance interfacial stability and further improve battery performance.

[0041] In some embodiments, the mass fraction of the third additive is 0.05% to 3% based on the total mass of the electrolyte, for example, 0.05%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2.1%, 2.5%, 3%, etc. Optionally, the mass fraction of the third additive is 0.1% to 0.5% based on the total mass of the electrolyte, for example, 0.1%, 0.2%, 0.35%, 0.4%, 0.5%, etc.

[0042] In some embodiments, a fourth additive is further included, which comprises at least one of lithium difluorobis(oxalato)phosphate, tris(trimethylsilyl)phosphate (TMSP), and lithium difluorophosphate. The fourth additive may work synergistically with the first and second additives to improve battery performance.

[0043] In some embodiments, a solvent is further included; the solvent includes at least one of carbonates and carboxylic esters. Exemplarily, the carbonate includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and fluoroethylene carbonate. Exemplarily, the carboxylic ester includes at least one of ethyl formate, ethyl acetate, propyl acetate, and ethyl propionate.

[0044] Based on the total mass of the electrolyte, the mass fraction of the solvent is 70% to 90%, for example, 70%, 72%, 76%, 78%, 80%, 90%, etc.

[0045] Optionally, the carbonate includes fluorocarbonate; the carboxylic acid ester includes fluorocarboxylic acid ester. In the solvent, the mass fraction of the fluorinated solvent is 60% to 90%, for example, 60%, 65%, 75%, 80%, etc.; wherein the fluorinated solvent includes at least one of carbonate and fluorocarboxylic acid ester.

[0046] In some embodiments, the carbonate comprises dimethyl carbonate; the mass fraction of the dimethyl carbonate is 10% to 40% based on the total mass of the electrolyte, for example 10%, 12%, 15%, 18%, 20%, 22%, 25%, 30%, 33%, 35%, 38%, or 40%.

[0047] In some embodiments, the electrolyte further includes lithium salts; lithium salts include lithium hexafluorophosphate (LiPF6), lithium bisfluorosulfonylimide (LiFSI), etc.

[0048] Furthermore, based on the total mass of the electrolyte, the mass fraction of lithium salt is 12% to 16%, for example, 12%, 13%, 15%, 16%, etc.

[0049] It should be noted that the lithium salt here can be a single lithium salt or a mixture of lithium salts. For mixed lithium salts, it can be lithium hexafluorophosphate and lithium bisfluorosulfonylimide, and the ratio of the two can be 14:1, 14:2, 13:2, etc.

[0050] Lithium battery This disclosure provides a lithium battery. In some embodiments, the lithium battery includes a positive electrode, a negative electrode, and the aforementioned electrolyte located between the positive and negative electrodes. During battery charging and discharging, active ions repeatedly insert and extract between the positive and negative electrodes. The electrolyte acts as a conductor of ions between the positive and negative electrodes.

[0051] Positive electrode sheet The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer including a positive electrode active material.

[0052] For example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0053] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (e.g., polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0054] In some embodiments, the positive electrode active material comprises a ternary positive electrode material. Optionally, in the ternary positive electrode material, the mass percentage of nickel is not less than 90% based on the total mass of metal elements other than lithium.

[0055] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0056] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0057] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0058] Negative electrode sheet The negative electrode includes a negative current collector and a film layer optionally disposed on at least one surface of the negative current collector.

[0059] For example, the film layer may include a negative electrode active material, a conductive agent, a thickener, and a binder.

[0060] In some embodiments, the negative electrode active material includes any one or a combination of at least two of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide, silicon-carbon composite material, or lithium titanate.

[0061] Optionally, the negative electrode active material is a mixture of silicon-carbon composite material and graphite. Here, based on the total mass of the negative electrode active material, the mass fraction of the silicon-carbon composite material is 5% to 35%, for example, 5%, 7%, 9%, 10%, 12%, 15%, 18%, 28%, 30%, or 35%. Here, the silicon content in the silicon-carbon composite material is not less than 20%.

[0062] In some embodiments, the negative electrode sheet can be prepared by dispersing the negative electrode active material, conductive agent, thickener, binder and any other components in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0063] Separator membrane In some embodiments, the secondary battery further includes a separator. This disclosure does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0064] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0065] Examples The following describes embodiments of this disclosure. The embodiments described below are exemplary and are only used to explain this disclosure, and should not be construed as limiting this disclosure. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0066] The specific preparation method of the secondary lithium-ion battery of Embodiment 1 of this disclosure is as follows: (1) Preparation of lithium nickel cobalt manganese oxygen cathode: The positive electrode active material (LiNi) 0.9 Co 0.05 Mn 0.05 O2), polyvinylidene fluoride as a binder, and Super P as a conductive agent are mixed in a mass ratio of 98:1:1. N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under vacuum to obtain a positive electrode slurry. The positive electrode slurry is then uniformly coated onto an aluminum foil. After the aluminum foil is dried at room temperature, it is transferred to an oven for drying. Then, it is cold-pressed and slit to obtain the positive electrode (electrode sheet).

[0067] (2) Preparation of silicon-carbon composite anode: A silicon-carbon composite material and graphite (mass ratio 20:80) were used as the negative electrode active material, Super P as the conductive agent, sodium carboxymethyl cellulose (CMC-Na) as the thickener, and styrene-butadiene rubber (SBR) as the binder. These were mixed at a mass ratio of 96:1:1:2, and deionized water was added. The mixture was stirred in a vacuum mixer to obtain a negative electrode slurry. The negative electrode slurry was then uniformly coated onto a copper foil current collector. After the copper foil was dried at room temperature, it was transferred to an oven for further drying. The resulting material was then cold-pressed and slit to obtain the negative electrode (electrode sheet). It should be noted that the silicon content in the silicon-carbon composite material is 40%.

[0068] (3) Preparation of electrolyte: In an argon-atmosphere glove box with a water content of <10 ppm, battery-grade ethyl 2,2-difluoroacetate (DFEA), fluoroethylene carbonate (FEC), and dimethyl carbonate (DMC) were mixed in a mass ratio of 5:1:2 to form a base solvent. Lithium hexafluorophosphate was then added. Based on the total mass of the electrolyte, each additive was formulated according to the mass percentages in Table 1, with the lithium hexafluorophosphate content being 12.5%, to obtain the electrolyte (i.e., Example 1 in Table 1).

[0069] In Table 1, the content of each component is a mass percentage calculated based on the total mass of the electrolyte. The electrolytes in other embodiments and comparative examples are prepared in the same manner as in this embodiment, except that the component ratios are as specified in Table 1. It should be noted that if the total content of all components in the electrolyte is less than 100%, it is supplemented by the base solvent.

[0070] It should be noted that, unless otherwise specified, the positive electrode active materials in the other embodiments and comparative examples are the same as those in Example 1.

[0071] (4) Preparation of the separating membrane: Polypropylene film is used as the separator.

[0072] (5) Preparation of secondary batteries: Using a 12μm thick polypropylene (PP) film as the separator, the prepared positive electrode, separator, and negative electrode are stacked sequentially, with the separator positioned between the positive and negative electrodes to provide isolation. Then, an aluminum-plastic film is wrapped around the separator, and the mixture is dried in a vacuum oven at 120°C. After injecting 3.0 g / Ah of the prepared electrolyte, the mixture is sealed and liquefied to produce a 1Ah soft-pack battery, i.e., a lithium-ion battery.

[0073] Test method The secondary batteries prepared in the above embodiments and comparative examples can be tested using the following methods, and the results are shown in Table 1.

[0074] (1) Capacity recovery rate after 60 days (2M) of storage at 60℃ At 25℃, the lithium-ion battery was charged at a constant current of 0.33C to 4.25V, then charged at a constant voltage to a current of 0.05C, allowed to stand for 30 minutes, and then discharged at a constant current of 0.33C to 2.5V. After two cycles, the final discharge capacity C1 was recorded. The fully charged battery was then stored in a 60℃ oven for 60 days. The cells were cooled, the oven temperature was adjusted to 25℃, allowed to stand for 10 minutes, and then discharged at a constant current of 0.33C to 2.5V. This was followed by two cycles of 0.33C charge / discharge within a voltage range of 2.5V-4.25V, and the final discharge capacity C2 was recorded. The capacity recovery rate of the lithium-ion battery relative to its initial value before storage was calculated using the following formula: Capacity recovery rate (%) = (C2 / C1) × 100%.

[0075] (2) Capacity retention rate after 500 cycles at 25°C Adjust the temperature of the constant temperature chamber to 25℃ and stabilize for 30 minutes; charge at a constant current of 1C to 4.25V, then charge at a constant voltage of 0.05C, let stand for 10 minutes, and then discharge at a constant current of 1C to 2.5V, recording the discharge capacity C3. Repeat this charge-discharge cycle 500 times, and record the discharge capacity C4 of the cell on the 500th cycle. The capacity retention rate after 500 cycles at 25℃ is: Capacity retention rate (%) = C4 / C3 × 100%.

[0076] (3) Initial Impedance (BOL DCR) Test Set the temperature of the constant temperature chamber to 25℃ and let it stand for 10 minutes. Charge it with a constant current of 0.33C to 4.25V, then charge it with a constant current of 0.05C at 4.25V and let it stand for 30 minutes. Discharge it with a constant current of 0.33C to 2.5V and let it stand for 10 minutes. Repeat this cycle twice and record the discharge capacity as C0. Charge it with a constant current of 0.33C to 4.25V, then charge it with a constant voltage of 0.05C and let it stand for 30 minutes. Discharge it with a constant current of 0.33C to 50% C0 and let it stand for 1 hour. Record the voltage V0 at the end of the standing period. Discharge it with a constant current of 4C0 for 30 seconds and record the voltage V1.

[0077] Initial impedance BOL DCR (mΩ) = (V0 - V1) / 4C0 Table 1. Electrolyte composition and lithium-ion battery performance test results for different groups of examples and comparative examples.

[0078] Comparing Comparative Examples 1-4 and Example 15, it can be seen that adding the compound shown in Formula (III) alone, the combination of the compound shown in Formula (III) and the third additive, and the combination of the second additive and the third additive alone are insufficient in improving the capacity of the battery after high-temperature storage and the capacity after room-temperature cycling, and also lead to a significant increase in the initial impedance of the battery. Simultaneous addition of the compound shown in Formula (III) and the second additive can significantly improve the capacity of the battery after high-temperature storage and the capacity after room-temperature cycling, even with a slight increase in the initial impedance. In other words, the synergistic effect of the compound shown in Formula (III) and the second additive helps to prepare a battery with better overall performance.

[0079] Comparing Comparative Example 2, Examples 1-5, and Comparative Example 6, it can be seen that, while keeping the amounts of the second and third additives constant, increasing the content of the compound shown in Formula (III) in the electrolyte results in a trend of first increasing and then decreasing capacity after high-temperature storage and after cycling at room temperature, while the initial impedance shows a trend of first decreasing and then increasing. Optionally, when the amount of the compound shown in Formula (III) added is 0.1% to 0.5%, the overall battery performance is even better.

[0080] Comparing Examples 4 and 14, and Examples 7 and 13, it can be seen that adding the compound shown in Formula (Ⅳ) to the electrolyte has similar technical effects to the compound shown in Formula (Ⅲ), and both can improve the overall performance of the battery.

[0081] Comparing Example 3 and Example 16, it can be seen that adding TMSP to the electrolyte can further improve the battery's performance after high-temperature storage and its cycle performance at room temperature, thus improving the overall performance of the battery.

[0082] Comparing Examples 3, 6-9, and 15, it can be seen that, while keeping the amounts of the compound shown in Formula (III) and the second additive constant, increasing the content of the third additive in the electrolyte results in a trend of first increasing and then decreasing the battery capacity after high-temperature storage and after cycling at room temperature. Optionally, when the amount of the third additive is 0.1% to 0.5%, the overall battery performance is better.

[0083] Comparing Comparative Example 4, Example 3, and Examples 10-12, it can be seen that, while keeping the amounts of the compound shown in Formula (III) and the third additive constant, increasing the content of the second additive in the electrolyte results in a trend of first increasing and then decreasing battery capacity after high-temperature storage and after cycling at room temperature. Adding 1% of the second additive allows the compound shown in Formula (III) and the second additive to work synergistically, significantly reducing the initial impedance. As the content of the second additive increases, the initial impedance gradually increases. Optionally, when the amount of the second additive is 5% to 10%, the overall battery performance is even better.

[0084] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of this disclosure (including the claims) is limited to these examples; within the framework of this disclosure, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of different aspects of the embodiments of this disclosure as described above, which are not provided in detail for the sake of brevity.

[0085] This disclosure is intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this disclosure should be included within the scope of protection of this disclosure.

Claims

1. An electrolyte, characterized in that, The electrolyte includes a first additive and a second additive; wherein... The first additive is a compound represented by the following formula (I): Equation (I); In formula (I), R is independently selected from any one of the following groups: hydrogen, halogen, cyano, silyl, substituted or unsubstituted amino, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, substituted or unsubstituted C1-C6 ester-containing group, substituted or unsubstituted C1-C6 carbonyl-containing group, and substituted or unsubstituted heterocyclic group from 3 to 8 members; when substituted, the substituent is selected from at least one of halogen, amino, cyano or silyl. The second additive is a compound as shown in formula (II): Formula (II).

2. The electrolyte according to claim 1, characterized in that, The heterocyclic group is selected from pyridine, cyclic carboxylic anhydride, or imidazole; and / or and / or Based on the total mass of the electrolyte, the mass fraction of the first additive is 0.05% to 3%, and the mass fraction of the second additive is 1% to 17%.

3. The electrolyte according to claim 1, characterized in that, Based on the total mass of the electrolyte, the mass fraction of the first additive is 0.1% to 0.5%; the mass fraction of the second additive is 5% to 10%.

4. The electrolyte according to claim 1, characterized in that, The compound represented by formula (I) includes at least one of the following structural formulas: Formula (Ⅲ), Formula (Ⅳ) Formula (V) Formula (VI).

5. The electrolyte according to claim 4, characterized in that, It also includes a third additive, which is a compound as shown in formula (VII): Formula (VII); Based on the total mass of the electrolyte, the mass fraction of the third additive is 0.05% to 3%.

6. The electrolyte according to claim 5, characterized in that, Based on the total mass of the electrolyte, the mass fraction of the third additive is 0.1% to 0.5%.

7. The electrolyte according to claim 1, characterized in that, It also includes a fourth additive, which includes at least one of lithium difluorobis(oxalato)phosphate, tris(trimethylsilyl)phosphate, and lithium difluorophosphate.

8. The electrolyte according to claim 1, characterized in that, It also includes a solvent; the solvent includes at least one of carbonates and carboxylic esters.

9. The electrolyte according to claim 8, characterized in that, The carbonate includes dimethyl carbonate; Based on the total mass of the electrolyte, the mass fraction of dimethyl carbonate is 10% to 40%.

10. A lithium battery, characterized in that, The lithium battery includes an electrolyte according to any one of claims 1 to 9 and a ternary cathode material; wherein, in the ternary cathode material, the mass percentage of nickel is not less than 90% based on the total mass of metal elements other than lithium.